Study of diversity of mineral-forming bacteria in sabkha mats and sediments of mangrove forest in Qatar - Toka Mahmoud Farhat (17017758) (2023)
The involvement of microorganisms in carbonate minerals and modern dolomite formation in evaporitic environments occupied with microbial mats (i.e., sabkha) and in mangrove forests is evidenced, while its potential diversity requires further elucidation. Microorganisms can create supersaturated microenvironments facilitating the formation of various carbonate minerals through specific metabolic pathways. This is particularly important in arid environments, where deposition and sedimentary structures can occur. This study investigated the biodiversity of halophilic, heterotrophic, and aerobic mineral-forming bacteria in mangrove forests and living and decaying mats of Qatari sabkha. The diversity study was performed at the protein level using MALDI-TOF mass spectrometry protein profiles combined with principal component analysis (PCA), which revealed a high diversity of isolated strains at the taxonomy and protein profile levels. The diversity of the minerals formed in pure cultures was evidenced by SEM/EDS and XRD analysis. Different types of carbonate minerals (calcium carbonate, magnesium carbonates, and high-magnesium calcites) were formed in pure cultures of the studied strains, which might explain their occurrence in the bulk composition of the sediments from where the strains were isolated. These results illuminate the diversity of biological mineral-formation processes in the extreme environments of Qatari sabkhas and mangroves, explaining the high diversity of minerals in these environments. Other Information Published in: Biotechnology Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.btre.2023.e00811